Improving Teachers' Capability in Writing Scientific Articles through Training and Mentoring in West Sumatera - Maksum, Hasan; Martias, Martias; Purwanto, Wawan; Arif, Ahmad; Putra, Dwi Sudarno; Setiawan, Yasep (Universitas Negeri Padang, 2024)
This analysis aims to determine whether instructors have the capability of transforming their classroom action research findings into academic papers. The interval between the pandemic and post-pandemic requires a strategy to ensure that the transition of learning stays on to provide students with solace in their educational experience during this time. Thirty attendees, all members of the West Sumatra Automotive Engineering Subject Teacher Meeting, participated in the event. The participants were separated into online and offline groups. To evaluate the extent of learning value, online modules created by participants will be analyzed to judge instructors' capability to develop the academic paper. Participants were able to construct effective learning as a result. For online participants, the mentor must spend additional time instructing them on how to complete the mission.